The Ecuadorian banking crisis: a different crisis? - Mancero, Daniel (2016)
This article attempts a comparative analysis of the Ecuadorian financial crisis in order to establish if its causes were similar to those that have produced other financial crises, and if its costs and duration will be comparable to these other crises. The author reveals the reasons that explain why the Ecuadorian financial crisis is not over, and what policies can correct its manifestations and prevent their recurrence.